PET/CT in diagnosis of dementia - Berti, Valentina (2011)
Clinical use of positron emission tomography (PET) is now well established in neurodegenerative disorders, especially in the diagnosis of dementia. Measurement of cerebral glucose metabolism is of significant value, and it facilitates early diagnosis, appropriate differential diagnosis, and the evaluation of drug treatment in patients with dementia. In addition, tracers offer new perspectives for studying the neuropathology of underlying dementia, such as the accumulation of amyloid proteins, tau-proteins, or the presence of neuroinflammation. Finally, PET tracer studies of different neurotransmitter systems in dementia may not only increase the understanding of pathophysiologic mechanisms of the different disorders, but also improve diagnostic accuracy. In conclusion, PET imaging with different tracers offers reliable biomarkers in dementia, which can assist clinicians in the diagnosis of different dementing disorders, especially in the situation of overlapping phenotypes.